PERANCANGAN RAK PENYIMPANAN DAN PEMOTONGAN KAIN ROLL UNTUK MEMPERBAIKI RISIKO POSTUR KERJA DI WORKSHOP MODESTY SOFA - Zalukhu, Vindi Shalsa Putri; Daywin, Frans Jusuf; Gozali, Lina (Universitas Tarumanagara, 2024)
Modesty Sofa is a company engaged in the furniture industry which produces various types of sofas. In the sofa-making production process, it is divided into two stations, namely the sofa frame manufacturing station and the sofa finishing station. The lack of adequate facilities such as cloth cutting tools which are still done manually on the floor causes a less ergonomic work posture. Based on the results of distributing the NBM questionnaire to 2 employees, it was found that employees felt pain in the neck, back, waist, shoulders, thighs, calves and feet. In the REBA analysis, a score of 5 (medium risk level) was obtained for the squatting work posture and a score of 8 (high risk level) for the kneeling work posture, and in the OWAS analysis, a score of 2 was obtained for the squatting and kneeling work posture. From the conditions described, it is necessary to design storage racks and roll cloth cutting which can improve employee work posture and make it easier for employees to find fabric materials. The results of the REBA assessment on standing work posture of employees after implementing storage rack work tools and cutting cloth rolls only got a score of 3 (low risk), and on the OWAS assessment, got a score of 1, which means the work posture is in a safe position.